The History curriculum in Zimbabwe: Wishlist versus realities on the ground (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
One historian once wrote that the best historians need stronger boots and not a big library, a testament to the fact that the best historians need to be on the ground and do research in order to find information. In many countries, the History teacher needs a strong heart, for they always have to straddle the line between teaching realistic history and kowtowing to the dictates of the syllabus, which in some cases has been bastardised by the political elite. While it is an accepted fact that history is always taught from the point of view of the victors, that mantra has been stretched to a ridiculous extent in some instances. This is not to say that the history curriculum has been stretched to irrelevance. In fact, the new history curriculum implemented in Zimbabwe is relevant but has largely been infected with unnecessary and unrealistic patriotic overtones. The job of the history teacher in Zimbabwe has generally been made more difficult by the large doses of patriotic “history” that they are now obliged to pass off as fact to learners at all stages of learning.
Keywords: historians; History teacher; realistic history; syllabus; political elite; history curriculum implemented in Zimbabwe; patriotic “history”